PS2:27 Antibodies to carbamylated vimentin in patients with systemic lupus erythematosus are associated with renal involvenment. (21st March 2018) - Spinelli, FR; Colasanti, T; Truglia, S; Pecani, A; Ceccarelli, F; Miranda, F; Moscarelli, E; Mancini, R; Perricone, C; Alessandri, C; Valesini, G; Conti, F
Abstract : Vimentin is a cytoskeletal protein expressed by mesenchymal cells, including endothelial and renal tubular cells. Antibodies to vimentin were described in 10%–53% of patients with Systemic Lupus Erythematosus (SLE). Vimentin has been proposed as a target of the in situ immune response in lupus nephritis. Post-translational modifications increase the immunogenicity of vimentin, as demonstrated by the detection of anti-modified-vimentin antibodies in rheumatoid arthritis. Carbamylation is a non-enzymatic post-translational modification (addition of a cyanate group on lysine and arginine residues), which has been linked to NETosis. The role of carbamylated vimentin (Car-Vim) as an antigenic target in SLE has not been evaluated yet. Aim of the study was to assess the prevalence of anti-Car-VIm and to investigate any association with clinical and serological features in SLE patients. We enrolled SLE diagnosed according to 1997 ACR criteria. Clinical features, autoantibodies profile and disease activity – according to SLEDAI 2K – were collected. Patients' sera were tested for anti- Car-Vim by a home-made enzyme-linked immunoassay. Data were expressed as mean ±standard deviation or median (interquartile range) when appropriate. Mann-Whitney and Chi square test were applied to investigate differences in anti-carbamylated vimentin prevalence and serum levels. P value<0.05 was considered statistically significant. We enrolled 109 SLE patients (102F:7M, mean age 39.4±12.6 years, mean disease duration 10.5±9.5 years, mean SLEDAI 2K 5±5.5). Table 1 summarises the main clinical and serological features. Overall, 30/109 patients (27.5%) were positive for anti-Car-Vim. The prevalence of anti-Car-Vim was significantly higher in patients with lupus nephritis (18/44) compared to those without (12/66) (41.8% vs 18.2%, p=0.006); moreover, anti-Car-Vim serum levels were significantly higher in patients with lupus nephritis [2561 (1783) OD] compared to those without [1970 (1123) OD; p=0.0178]. No difference was found in prevalence or titre of anti-Car-Vim in presence/absence of other clinical or serological manifestations. No correlation between anti-Car-Vim serum levels and SLEDAI 2K was found. Higher prevalence and serum levels of anti-carbamylated vimentin antibodies in patients with lupus nephritis confirm the role of vimentin as a target of the immune response in glomerulonephritis and suggest their possible role as a biomarker of kidney involvement in SLE.